2018
DOI: 10.1111/acel.12754
|View full text |Cite
|
Sign up to set email alerts
|

nNOSCAPON interaction mediates amyloid‐β‐induced neurotoxicity, especially in the early stages

Abstract: SummaryIn neurons, increased protein–protein interactions between neuronal nitric oxide synthase (nNOS) and its carboxy‐terminal PDZ ligand (CAPON) contribute to excitotoxicity and abnormal dendritic spine development, both of which are involved in the development of Alzheimer's disease. In models of Alzheimer's disease, increased nNOS–CAPON interaction was detected after treatment with amyloid‐β in vitro, and a similar change was found in the hippocampus of APP/PS1 mice (a transgenic mouse model of Alzheimer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Notably, p38 MAPK activity was linked to amyloid b (Ab )-induced spine loss driven by non-ionotropic NMDAR signaling (Birnbaum et al, 2015). In addition, increased nNOS-NOS1AP interaction was detected after treatment with Ab in vitro and in APP/PS1 mice in vivo (Zhang et al, 2018b). After blocking the nNOS-NOS1AP interaction, memory was rescued in 4-month-old APP/PS1 mice, and dendritic impairments were ameliorated both in vivo and in vitro (Zhang et al, 2018b), further supporting a role for non-ionotropic NMDAR signaling in Alzheimer's disease.…”
Section: Non-ionotropic Nmdar Signaling In Diseasementioning
confidence: 85%
See 1 more Smart Citation
“…Notably, p38 MAPK activity was linked to amyloid b (Ab )-induced spine loss driven by non-ionotropic NMDAR signaling (Birnbaum et al, 2015). In addition, increased nNOS-NOS1AP interaction was detected after treatment with Ab in vitro and in APP/PS1 mice in vivo (Zhang et al, 2018b). After blocking the nNOS-NOS1AP interaction, memory was rescued in 4-month-old APP/PS1 mice, and dendritic impairments were ameliorated both in vivo and in vitro (Zhang et al, 2018b), further supporting a role for non-ionotropic NMDAR signaling in Alzheimer's disease.…”
Section: Non-ionotropic Nmdar Signaling In Diseasementioning
confidence: 85%
“…Notably, NOS1AP is important for nNOS-mediated nitrosylation of Dexras1, a small GTPase that negatively regulates the MAP kinase Erk (Zhu et al, 2014;Zhang et al, 2018b). Thus, the dual and opposite regulation of p38 and Erk MAPK activities through NOS1AP would allow NOS1AP to locally activate p38 MAPK-dependent LTD and spine shrinkage signaling pathways, and at the same time downregulate Erk-dependent LTP signaling (Zhu et al, 2002;Zhang et al, 2018a).…”
Section: Nos1ap and Nnosmentioning
confidence: 99%
“…Also, stroke, neuropathic pain and early‐stage Alzheimer's disease are associated with the co‐morbid anxiety (Bierman, Comijs, Jonker, Scheltens, & Beekman, 2009; Campbell Burton et al, 2013; Knapp et al, 2017; Kwak, Yang, & Koo, 2017; Nicholson & Verma, 2004). Reportedly, nNOS–CAPON association mediates amyloid‐β‐induced neurotoxicity (Zhang et al, 2018), ischaemia‐induced impairment of structural plasticity (Ni et al, 2018) and inflammatory nociception and chemotherapy‐induced neuropathic pain (Lee, Carey, et al, 2018; Lee, Li, et al, 2018). We previously reported that dissociation of nNOS with CAPON by ZLc‐002 produces rapid onset of anxiolytic‐like effect (Zhu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that nNOS activity is required for NOS1AP recruitment during excitotoxicity and that the interaction with NOS1AP also is important for nNOS-mediated nitrosylation of Dexras1, which negatively regulates Erk (Zhu et al, 2014;Zhang et al, 2018b). Thus, this dual and opposite regulation of p38 and Erk MAPK activity through NOS1AP, if occurring during non-ionotropic NMDAR signaling, would allow NOS1AP to locally activate p38 MAPK-dependent LTD and spine shrinkage signaling pathways and at the same time downregulate Erk-dependent LTP signaling (Zhu et al, 2002;Zhang et al, 2018a).…”
Section: Nos1ap and Nnosmentioning
confidence: 99%
“…Notably, p38 MAPK activity was linked to amyloid beta (Aβ)-induced spine loss driven by non-ionotropic NMDAR signaling (Birnbaum et al, 2015). In addition, in models of Alzheimer's disease, increased nNOS-NOS1AP interaction was detected after treatment with Aβ in vitro and in APP/PS1 mice in vivo (Zhang et al, 2018b). After blocking the nNOS-NOS1AP interaction, memory was rescued in 4-month-old APP/PS1 mice, and dendritic impairments were ameliorated both in vivo and in vitro (Zhang et al, 2018b), further supporting a possible role for non-ionotropic NMDAR signaling in Alzheimer's disease.…”
Section: Non-ionotropic Nmdar Signaling In Diseasementioning
confidence: 99%